The Effect of Leadership, Ability, and Work Motivation on Employee Performance: Case Study of Agriculture Office, Wajo Regency, Indonesia - Nurfadillah, N.; Serang, Serlin; Imaduddin, I. (Manunggal Halim Jaya, 2025)
This study aims to analyze the effect of leadership style, workability, and work motivation on employee performance at the Wajo Regency Agriculture and Food Security Office. The main hypothesis tested is that the three variables have a positive and significant effect on employee performance. This research uses a quantitative approach with data collection methods through questionnaires distributed to 60 employees as research samples. Data analysis was performed using multiple linear regression, validity, reliability, and classical assumption tests. The results showed that leadership style, workability, and work motivation have a significant positive influence on employee performance. These findings emphasize the importance of inclusive leadership, employee placement according to ability, and strong motivation from within and the work environment to improve performance. This research implies the need to improve the quality of leadership and human resource management in government agencies to achieve optimal performance. Further research is recommended to involve other variables, such as work environment and compensation, as well as expanding the number of samples and research context to gain a more comprehensive understanding.